2022
DOI: 10.1021/acschemneuro.2c00124
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Intranasally Administrated Oxytocin-Loaded Nanoparticles on Pentylenetetrazole-Kindling Epilepsy in Terms of Seizure Severity, Memory, Neurogenesis, and Neuronal Damage

Abstract: Pentylenetetrazole (PTZ)-induced kindling is an animal model for studying human temporal lobe epilepsy (TLE), which is characterized by alterations of hippocampal neurons and memory. Although the intranasal (IN) administration of oxytocin (OT) has limited efficiency, nanoparticles (NPs) are a promising candidate to deliver OT to the brain. However, there are very limited data on epilepsy research about oxytocin-loaded nanoparticles (NP-OTs). The aim of this study is to investigate the effects of IN administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Another analysis showed increased neurogenesis and decreased apoptosis in the hippocampal region following OXT-NPs. Hence, authors concluded that OXT-NPs may have a positive effect on the Pentylenetetrazole-induced epilepsy; however, more research is needed to examine total antioxidant capacity and total oxidant capacity in the serum (Sahin et al, 2022).…”
Section: Nanocarriers Enabled Delivery Of Peptide Therapeutics In Var...mentioning
confidence: 99%
“…Another analysis showed increased neurogenesis and decreased apoptosis in the hippocampal region following OXT-NPs. Hence, authors concluded that OXT-NPs may have a positive effect on the Pentylenetetrazole-induced epilepsy; however, more research is needed to examine total antioxidant capacity and total oxidant capacity in the serum (Sahin et al, 2022).…”
Section: Nanocarriers Enabled Delivery Of Peptide Therapeutics In Var...mentioning
confidence: 99%